Around value contemporary youth - Joanna Smyła (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The article is related to the issues of values appreciated by modern youth. Nowadays, it is particulary essential, when we a move from traditional societies towards post-modern ones as well as rapidly changing and unpredictable reality. In 2018, I conducted a research to find out the values appreciated by today's youth. A group of 372 high school students from the Podkarpackie province participated in my research. I used the diagnostic survey method and the survey technique. The values of health and happiness as well as freedom and independence take the most important place. This condition seems understandable in the development of youth and democracy. Family and work are also extremely important in the respondents' lives, which may be a result of market economy impact. What is more, the high positions are taken by education and education background. The values declared by young people are optimistic. However, it should be remembered that the value system may undergo changes. As a result, they should be followed due to the fact that economic, scientific and technical progress of the country will depend on the moral state of young people in the near future.